Payment schemes in conditional cash transfer programs: The case of 4Ps in the Davao Region, Philippines - Ma Cecilia Catubig; Renato Villano; Brian Dollery (Administrative Sciences, 2015)
This paper evaluates current payment schemes employed by the Pantawid Pamilyang Pilipino Program (4Ps) in the Philippines using six assessment criteria: transaction cost, security/risks, speed and timeliness, acceptability, resilience and flexibility. Employing data collected at the regional level, we establish four main findings: (1) all 4Ps payment conduits present trade-offs; (2) a payment approach that uses mainstream financial infrastructure is beneficial if cost, speed and simplicity of the payment system are critical; (3) competition for 4Ps contracts for Payment Service Providers (PSPs) has improved the quality of payment services and minimized costs; and (4) the efficiency of the program is greatly influenced by the commitment of the PSP to deliver the cash benefits to the recipients in a timely manner rather than by maximizing conduit branches.
Keywords: 350; conditional cash transfer; 4Ps; Philippines; payment service providers